ANALISIS TRANSPORTASI KAWASAN NIAGA PANGLIMA BATUR KOTA SAMARINDA - Tukimun Tukimun; Rosa Agustaniah (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2023)
The Panglima Batur Commercial Area is a shopping area which is the center of commercial activity in Samarinda City. Around Jalan Panglima Batur there are several shopping centers such as Pasar Pagi, Mesra Indah Mall, shops along Jalan Panglima Batur and the Citra Niaga Commercial Area which is a